2016
DOI: 10.1098/rsta.2016.0050
|View full text |Cite
|
Sign up to set email alerts
|

Organic dyes in illuminated manuscripts: a unique cultural and historic record

Abstract: One contribution of 14 to a theme issue 'Raman spectroscopy in art and archaeology'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…Raman spectroscopy was also applied to the identification of dyestuffs used for colouring the banknotes. Previous reports on the analysis of natural dyes such as indigo, [29,30] brazilwood, [31] or luteolin, [32] showed that Raman spectroscopy can be used as a tool for the characterization and identification of dyestuffs. However, the main drawback of its application is the strong fluorescence signal, which can be, in many cases, the dominant feature in the spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Raman spectroscopy was also applied to the identification of dyestuffs used for colouring the banknotes. Previous reports on the analysis of natural dyes such as indigo, [29,30] brazilwood, [31] or luteolin, [32] showed that Raman spectroscopy can be used as a tool for the characterization and identification of dyestuffs. However, the main drawback of its application is the strong fluorescence signal, which can be, in many cases, the dominant feature in the spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the set of pigments used in manuscript illumination is relatively limited, and well-studied, making it possible to confidently identify examples of the most commonly encountered pigments, pigment mixtures, and painting techniques [31,32,33,34,35]. For example, purple pigments can be derived from natural materials such as mollusks, lichens or dye plants, or by using mixtures of blue pig-ments (e.g.…”
Section: Data and Experimental Setupmentioning
confidence: 99%
“…Due to the molecular emission properties of red lakes, another potential mapping method is based on fluorescence. Microspectrofluorimetry has been used for lake pigment analysis on illuminated manuscripts and other artworks . These studies showed the need for analyzing reference paints in order to identify fluorescence spectral features characteristic of the lake.…”
Section: Introductionmentioning
confidence: 99%